(untitled) - Melvin, Michael (Reading, Massachusetts, 1996)
The book can be thought of in terms of three main sections. Section one (chapters 1 through 8) identifies the key institutions and relationships of the international monetary system. In this section, the book offers an understanding of the relationships among prices, exchange rates, and interest rates. Section two (chapters 9 through 10) covers the next general area of the determinants of balance of payments and exchange rates. Government and industry devote many resources to trying to forecast the balance of payments and exchange rates. The discussion in this section includes the most important recent developments. Section three (chpaters 11 through 13) is devoted to applied topics of interests to the international financial manager. Issues range from the "nuts and bolts" of financing imports and exports to the evaluation of risk in international lending to sovereign governments. The topics covered in this section is of practical interest to corporate treasurers and international bankers. The concluding chapter is an analysis of macroeconomic issues in an open economy. This coverage of open-economy macroeconomics includes the determination of the equilibrium values of key macroeconomic variables and the effects of government monetary and fiscal policy on these variables
Tài chính quốc tế
Keywords: International finance,Tài chính quốc tế